ANALISIS FAKTOR KETIDAKPUASAN, FITUR PRODUK, HARGA, DAN WORD OF MOUTH TERHADAP BRAND SWITCHING PADA PRODUK SMARTPHONE OPPO - Eny Kustiyah, Soni Dewantara, Bambang Mursito & (Universitas Slamet Riyadi, 2018)
The phenomenon of displacement behavior of the brand (brand switching) toevaluation is important for every company, to avoid losing customers and going forwardto reach new consumers. The purpose of this research is to know the influence factor ofdissatisfaction, product features, pricing, and word of mouth against brand switching onOppo smartphone products. The respondents in this study are students who are usuallymore in the use of smartphones with a sample of 100 respondents, sampling techniquethat is purposive sampling. Quantitative methods with questionnaires used to collectdata. Using multiple linear regression analysis tool. The analysis of the F-test describesa factor dissatisfaction, product features, price, and word of mouth effect simultaneouslyagainst brand switching on Oppo smartphone products. Through the t-test, thatdissatisfaction has no effect and does not significantly to brand switching on Opposmartphone products. Product features influential and significantly to brand switchingon Oppo smartphone products. Price influential and significantly to brand switching onOppo smartphone products. Word of mouth has no effect and does not significantly tobrand switching on Oppo smartphone products. Of all the variables, contributed 51%obtained from the determination of the test results (adjusted R2), the remaining 49% arenot described in this study.Keywords: dissatisfaction, product features, price, word of mouth, brand switching